'College radio': The development of a trope in US student broadcasting. Issue 1 (1st March 2015) - Rubin, Nick
In the United States, the term 'college radio' invokes a specific, influential subset of student radio. In the early 1980s, 'college radio' appeared in popular discourse to refer to non-profit student stations which championed music marginalized by mainstream, commercial radio. College radio programming enacted a critique of the music industry's political economy, reflecting participation in the late 1970s and early 1980s Do-It-Yourself (DIY) rock underground, an association of independent labels; independent record stores; small clubs; 'zines; and those college stations which embraced punk and its offshoots. This subcultural identification carried tensions, namely, college stations functioned within the music industry they often sought to critique. As college radio communities negotiated this terrain, they helped shape 'alternative' and 'indie' culture – loosely defined but emblematic subsets of late twentieth-century US popular culture. Here, I examine the development and deployment of the 'college radio' signifier in the US public sphere, review the existing academic literature on the sector and suggest avenues of future research.